Exploring Landmark Placement Strategies for Topology-Based Localization in Wireless Sensor Networks. (13th April 2008) - Benbadis Benbadis, Farid Farid; Obraczka Obraczka, Katia Katia; Cortés Cortés, Jorge Jorge; Brandwajn Brandwajn, Alexandre Alexandre
Abstract : In topology-based localization, each node in a network computes its hop-count distance to a finite number of reference nodes, or "landmarks". This paper studies the impact of landmark placement on the accuracy of the resulting coordinate systems. The coordinates of each node are given by the hop-count distance to the landmarks. We show analytically that placing landmarks on the boundary of the topology yields more accurate coordinate systems than when landmarks are placed in the interior. Moreover, under some conditions, we show that uniform landmark deployment on the boundary is optimal. This work is also the first empirical study to consider not only uniform, synthetic topologies, but also nonuniform topologies resembling more concrete deployments. Our simulation results show that, in general, if enough landmarks are used, random landmark placement yields comparative performance to placing landmarks on the boundary randomly or equally spaced. This is an important result since boundary placement, especially at equal distances, may turn out to be infeasible and/or prohibitively expensive (in terms of communication, processing overhead, and power consumption) in networks of nodes with limited capabilities.